Pengaruh Model Pembelajaran Probing Promting terhadap Prestasi Belajar Siswa pada Pelajaran Fisika dengan Materi Konsep Getaran Dan Gelombang Kelas X Jurusan Asisten Keperawatan SMK Negeri 11 Muaro Jambi - Yan Febri (Universitas Batanghari Jambi, 2021)
The aim of this research is to know how the Effect of The Technique Probing to Students Learning Outcomes in Study Conception Wave and Vibration. This Research has been at class x Nursing Assistant Departmen SMKN 11 Muaro Jambi To get the data, the research took 24 students as a sample by using Purpsive Sampling technique, after that the class was divided into two group, i.e. experiments and control classes. The instrumentation of this research used an objective multiple choice test. This test was consisted of four options, and the result of this test had been tested through t- test statistic. The calculation of tcount was 2,10 and ttable was 1,99; and 0,05 on the significant level or tcount > ttable. The conclusion is Ha that explained there are any Effect of The Technique Probing to Students Learning Outcomes in Study Conception Wave and Vibration accepted or agreed. This indicated that Effect of The Technique Probing brings the significant influence to the learning output.